Drought, Water Law, and the Origins of California's Central Valley Project - Stroshane, Tim, 1957- (Book collections on Project MUSE., 2016)
"Economic and political power in California's water system was born of monopolist Miller & Lux's water rights: they are ghostly and forgettable in the wet years, vexing and implacable in the dry. Drought, Water Law, and the Origins of California's Central Valley Project tells how drought and legal conflict shaped statewide economic development, and how a grand bargain from the monopolized bloc of water rights was struck, setting the stage for future water wars"--Provided by publisher.